Anonymus and Master Roger - CJ Nicholson (Slovo, 2012)
Nicholson, CJ (2012) Anonymus and Master Roger. [Series: Central European Medieval Texts.] Edited, translated and annotated by JÁNOS M. BAK, MARTYN RADY and LÁSZLÓ VESZPRÉMY. Pp. 268. Budapest and New York: Central European University Press. 2010. 55.00. £40.00. Cloth. ISBN 9789639776951. [Review]. Slovo, 24 (2). Click here to read the review.